Design and experiments of two-stage intercooled electrically assisted turbocharger. (1st March 2016) - Grönman, Aki; Sallinen, Petri; Honkatukia, Juha; Backman, Jari; Uusitalo, Antti
Highlights: New electrically assisted turbocharger concept is presented and measured. A 2.5% diesel engine efficiency improvement potential is predicted. Measurements show the potential of the machine. Abstract: The demand for continually improving the efficiency of large diesel engines requires increasing the pressure ratio and efficiency of turbochargers. One answer to these requirements is to use two-stage electrically assisted turbochargers, which will enable higher pressure ratios than before but also generate electricity in sufficient operating conditions. This study shows the design and experimental performance of the novel two-stage single-shaft electrically assisted turbocharger. It was predicted that an increase of 2.5 percentage points in overall efficiency can be achieved by using a two-stage single-shaft intercooled electrically assisted turbocharger in a 1200 kW diesel engine instead of a conventional single-stage turbocharger. It is experimentally shown that the studied turbocharger has potential for improving the engine efficiency although the performance was below the expected. Additionally, the critical points for the design improvements are assessed to guide future development work.